GLONASS observation of artificial field‐aligned plasma irregularities near magnetic zenith during EISCAT HF experiment - Sato, Hiroatsu; Rietveld, Michael; Jakowski, Norbert (Geophysical Research Letters, 2021)
We report on simultaneous observation of artificial plasma density irregularities near the magnetic zenith (MZ) by incoherent scatter radar and GNSS satellite in the high latitude. During an EISCAT (European Incoherent Scatter Scientific Association) HF heating experiment, a GLONASS satellite signal intersected the disturbed ionospheric volume along the local magnetic field lines. The satellite signal amplitude and phase were simultaneously perturbed when the electron temperature increased in the F region through O‐mode HF waves. The field‐aligned irregularities (FAIs) and associated density perturbations are most significantly found in the MZ direction. The growth of FAI reached the saturation level in 30 seconds while large scale electron density perturbation on the order of 0.1 TECU developed in a few minutes. The observed density perturbations agree well with recent numerical studies of FAI generation due to the thermal self‐focusing process.